Oxidative stress in the etiology of age-associated decline in glucose metabolism - Salmon, Adam B (BioMed Central, 2012)
One of the most common pathologies in aging humans is the development of glucose metabolism dysfunction. The high incidence of metabolic dysfunction, in particular type 2 diabetes mellitus, is a significant health and economic burden on the aging population. However, the mechanisms that regulate this age-related physiological decline, and thus potential preventative treatments, remain elusive. Even after accounting for age-related changes in adiposity, lean mass, blood lipids, etc., aging is an independent factor for reduced glucose tolerance and increased insulin resistance. Oxidative stress has been shown to have significant detrimental impacts on the regulation of glucose homeostasis in vitro and in vivo. Furthermore, oxidative stress has been shown to be modulated by age and diet in several model systems. This review provides an overview of these data and addresses whether increases in oxidative stress with aging may be a primary determinant of age-related metabolic dysfunction.